Ḥuqūq al-Mīrāth lināqil al-‘Adwā bi Fairūs Kūrūnā (Kūfīd-19) fī Manẓūr al-Sharī‘ah al-Islāmiyah wa al-Qānūn al-Indūnīsīyī (State Islamic University (UIN) of Sunan Ampel Surabaya, 2021)
Islamic law, as well as Indonesian law, prohibits the intentional killer's entitlement to inheritance and bequest to him. This research aims to study the ruling on the felony of murder by transmitting Coronavirus (Covid-19) infection. Subsequently, the impact of inheritance and wills due to transmitting this infection deliberately or unintentionally. The research uses the descriptive approach and the analytical method in defining the felony of incapacitating murder and analyzing the impact of transmitting infection with this pandemic virus. The research comes with several results, including that whoever deliberately transmits infection with the Coronavirus (Covid-19) to people is regarded as the Spoilers on the land, that this felony deserves the punishment, that he is forbidden from inheriting if he is the heir, and that he is forbidden from the approval of the will if it is bequeathed to him.